(untitled) (Bangladesh Journal of Medical Science, 2014)
Rhizoctonia solani is a very common soil borne pathogen with a great diversity of host plants. A 52 year old lady presented with sole manifestation of subcutaneous swelling over the left leg for 3 months Pus was collected by aspiration revealed septate fungal hyphae. After culture on SDA at 25 C showed white cottony growth initially, progressed to buff colored to black colonies on further incubation. On LPCB mount we found septate hyphae with acute and right angled branching without any conidia and hyphal anastomosis which resembled features of Rhizoctonia solani. Patient was put on Fluconazole and responded well to the treatment. DOI: http://dx.doi.org/10.3329/bjms.v13i2.15060 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.228-230